Global neonatal perioperative mortality: A systematic review and meta-analysis - Braz, Leandro Gobbo [UNESP]; Braz, Jose Reinaldo C. [UNESP]; Tiradentes, Teofilo Augusto A. [UNESP]; Soares, Joao Vitor A. [UNESP]; Corrente, Jose E. [UNESP]; Modolo, Norma Sueli P. [UNESP]; do Nascimento Junior, Paulo [UNESP]; Braz, Mariana Gobbo [UNESP] (Elsevier, 2024)
Study objective: There are large differences in health care among countries. A higher perioperative mortality rate (POMR) in neonates than in older children and adults has been recognized worldwide. The aim of this study was to provide a systematic review of published 24-h and 30-day POMRs in neonates from 2011 to 2022 in countries with different Human Development Index (HDI) levels. Design and setting: A systematic review with a meta-analysis of studies that reported 24-h and 30-day POMRs in neonates was performed. We searched the databases from January 2011 to July 30, 2022. Measurements: The POMRs (per 10,000 procedures under anesthesia) were analyzed according to country HDI. The HDI levels ranged from 0 to 1, representing the lowest and highest levels, respectively (very-high-HDI: ≥ 0.800, high-HDI: 0.700–0.799, medium-HDI: 0.550–0.699, and low-HDI: < 0.550). The magnitude of the POMRs by country HDI was studied using meta-analysis. Main results: Eighteen studies from 45 countries were included. The 24-h (n = 96 deaths) and 30-day (n = 459 deaths) POMRs were analyzed from 33,729 anesthetic procedures. The odds ratios (ORs) of the 24-h POMR in low-HDI countries were higher than those in very-high- (OR 8.4, 95% CI 1.7–40.4; p = 0.008), high- (OR 7.3, 95% CI 2.2–24.4; p = 0.001) and medium-HDI countries (OR 7.7, 95% CI 3.1–18.7; p < 0.0001) but with no odds differences between very-high- and high-HDI countries (p = 0.879), very-high- and medium-HDI countries (p = 0.915) and high- and medium-HDI countries (p = 0.689). The odds of a 30-day POMR in low-HDI countries were higher than those in very-high-HDI countries (OR 6.9, 95% CI 1.9–24.6; p = 0.002) but not in high-HDI countries (OR 1.4, 95% CI 0.6–3.0; p = 0.396). Conclusions: The review demonstrated very high global POMRs in a surgical population of neonates independent of the country HDI level. We identified differences in 24-h and 30-day POMRs between low-HDI countries and other countries with higher HDI levels.
Keywords: Anesthesia; High-income population; Low-income population; Mortality; Newborn; Surgery